Academic research, publishing and writing : critical thinking and strategies for business scholars - Dumay, John (Emerald Publishing Limited, 2024)
Academic Research, Publishing and Writing: Critical Thinking and Strategies for Business Scholars is designed for all scholars of business and management and outlines practical and proven ways of designing, developing, and executing impactful research and writing projects with a view to eventual publication. Chapters examine a wide range of essential scholarly practices in depth, including critical thinking and the IDEALS Framework, undertaking literature reviews, designing research for reliability, validity and generalisations, and understanding writing structure using IDEALS. John Dumay draws on experience and proven strategies to help the reader plot what they are going to research, what the potential impact of that research should be, what are the critical outlets for publishing are, and how should the research be written for the target audience. At the projects core is a strong focus on the importance on developing a strategy before starting the research which will increase the chances of publishing in high quality outlets, and surviving in the 'publish or perish' world.